Experimental observation and thermodynamic modeling of non-ideal expanding flows of siloxane MDM vapor for ORC applications. (1st February 2019) - Spinelli, Andrea; Cammi, Giorgia; Conti, Camilla Cecilia; Gallarini, Simone; Zocca, Marta; Cozzi, Fabio; Gaetani, Paolo; Dossena, Vincenzo; Guardone, Alberto
Abstract: This paper reports extensive experimental results characterizing the supersonic expansion of an organic vapor in non-ideal thermodynamic conditions typical of organic Rankine cycle (ORC) turbines. Data are also employed to assess the accuracy of different thermodynamic models used to describe non-ideal expansions. Experiments were carried out on a converging-diverging nozzle test section, where siloxane vapor MDM expanded in the proximity of the saturation curve, the typical operating region of ORC expanders, thus proving the importance of the present investigation for ORC technology. Indeed, detailed experimental data representative of ORC expansions, useful for design tool assessment, were lacking in the open literature up to date. Two nozzles, featuring exit Mach number of 2.0 and 1.5, were tested from highly non-ideal states to dilute gas conditions. The nozzle flow was characterized by measuring total pressure, total temperature and static pressure along the axis. The Mach number was measured at the centerline through schlieren imaging. Vapor expansion was found to be dependent on inlet conditions, thus proving the flow non-ideality. State-of-the-art thermodynamic models proved their capability of fully describing the flow non-ideality, while simpler and easier to implement equations of state, such as van der Waals, can be acceptable for preliminary expander calculations.